Building a more intimate connection between spirituality and quality service performance at work / Mazni Saad ... [et al.] - Saad, Mazni; Ahmad Shah, Norliana; Mohamed Mohan, Noor Malinda; Poniran, Halimi (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, Shah Alam, 2019)
One of the biggest challenges in tertiary education is that lecturers need to be versatile and able to quickly adapt to different challenges in many different functions or activities such as recruiting new student. Moreover, a higher timetable load may contribute to emotional stress, and  lecturers need to know how to work with unpredictable situations like difficult students or office politics. Thus, lecturers need a huge support system in place to deal with these situations at work, but information on lecturers’ coping abilities, specifically referred to as spiritual intelligence (SQ) is limited and not yet understood. Therefore, this study aims to examine how the SQ affects performance of lecturers in privately-owned universities by measuring the quality services. Based on the questionnaires distributed to lecturers in selected privately-owned universities, this study found that the SQ level among the young lecturers was quite high. It was also revealed that all sub-dimensions of SQ were positive and also significantly affected the performance of the lecturers. The standardised coefficient beta values indicated that the sub-dimensions of Transcendence contributed to 37%, while Meaning contributed to 31% Service Quality.